The Japanese firm : The sources of competitive strength - Aoki, Masahiko; Dore, Ronald (Oxford Oxford University Press, 2008)
A collection of interdisciplinary studies on Japanese firms, examining their diverse structures and management practices, and discussing the sources, complexity, and transferability of their competitive strength.
Keywords: Quản trị kinh doanh